Ефекти сумпора на компоненте приноса, принос семена и садржај уља репице (Брассица напус Л.) - Rameeh, Valiollah (Journal of Agricultural Sciences (Belgrade), 2021)
The effects of four sulphur levels: S0, S1, S2 and S3 included 0, 12, 24 and 36 kg S /ha, respectively along with 115 kg N /ha were studied on yield associated traits of rapeseed (Brassica napus L.). Significant mean square of treatments determined for the traits including plant height, yield components, seed yield and oil content. Sulphur application significantly increased most of the traits over S0 level. The S3 (36 kg S/ha) treatment produced the tallest plant (132 cm) which was classified with S2 (24 kg S/ha) as the same statistical group. Sulphur had increasing effect on pods per plant and it ranged from 92 to 196 for S0 and S3 application, respectively. S0 and S1 with 92 and 121 pods per plant were the same statistical group and also S2 and S3 with 165 and 196 pods per plant had not significant statistical difference. Sulphur application significantly increased seed yield over control (S0 level) and it ranged from 2744 to 3215 kg /ha in S0 and S3, respectively. An average oil content 45.69, 46.96, 47.46 and 49.53 % was found in treatments in which the doses of Sulphur of 0, 12, 24 and 36 were applied.
Keywords: Сумпор, семе репице, компоненте приноса и садржај уља